Biochemical and immune response in red tilapia (Oreochromis mossambicus × O. niloticus) with dietary chitosan supplementation - Méndez-Martínez, Yuniel; Pacheco-Morales, Ginger K.; Del Barco-Ibarra, Karla A.; Torres-Navarrete, Yenny G.; Hernández-Vergara, Martha P. (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
The use of biostimulants in fish diets is a promising strategy to reduce the use of antibiotics, enhance the biochemical and immune response, which contributes to improving productive yields and reducing economic losses. The biochemical and immune response was evaluated in juvenile red tilapia (Oreochromis mossambicus × ​​O. niloticus), with different levels: 0 (control), 1, 2, 3, 4 and 5% chitosan in diet. 270 animals (7.53 ± 0.50 g of initial weight), distributed in a completely randomized design of 6 treatments with 3 replicates and 45 tilapia.treatment-1, were sown in 18 tanks with 90 L of water in a closed system. The juveniles were fed for 55 days with the experimental diets and at the end of the bioassay the tissue and blood plasma samples were taken. Differences were found (p<0.05) in the variables evaluated responses, where the content of lipids, triglycerides, cholesterol, carbohydrates and glucose showed higher levels (p<0.05) at lower chitosan concentrations. However, for protein content, a better response (p<0.05) was found at higher levels of chitosan in the diet. Regarding dry matter and ash, no differences were found (p˃0.05). While superoxide dismutase and leukocytes were found in higher concentration (p<0.05) when supplemented with chitosan by 3 and 4%. It was concluded that the juvenile biochemical and immune response of red tilapia was favored with dietary chitosan supplementation.